Vacuum Nanoelectronic Devices : Novel Electron Sources and Applications /: Novel Electron Sources and Applications. (2015) - Evtukh, Anatoliy; Hartnagel, Hans, 1934-; Yilmazoglu, Oktay; Mimura, Hidenori; Pavlidis, Dimitris
No abstract available